The Effect of Gamilab Learning Media on Students' Arabic Language Learning Outcomes: Pengaruh Media Pembelajaran Gamilab terhadap Hasil Belajar Bahasa Arab Siswa - Fatimah Zahrah; Nabila Umayrah; Diva Prima Aisyahrani; Mawar Udin; Fita Umainah; Agung Setiyawan; Khuloud Alouzi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2026)
This study aimed to determine the effect of using the Gamilab application on Arabic language learning outcomes among tenth-grade students at MAN 3 Tanah Datar. The study was motivated by low learning outcomes among students in Arabic subjects and the limited use of interactive, technology-based learning media in schools. The research employed a quantitative pre-experimental design, specifically the One-Group Pretest-Posttest Design. The research sample consisted of all tenth-grade students (28), selected through a total sampling technique. Data were collected using pretest and posttest instruments and analyzed using a paired-samples t-test in SPSS. The results showed a significant difference between the pretest mean score of 50.00 and the posttest mean score of 88.68. The t-test significance value of p < 0.001 (< 0.05) indicated that the use of the Gamilab application had a significant effect on improving students' Arabic learning outcomes. Preliminary evidence from this study suggests that gamification-based platforms may enhance language learning outcomes. It indicates a positive contribution to the integration of interactive technology in Arabic language instruction. These findings offer theoretical implications for the development of digital learning media frameworks, particularly in the context of technology-mediated language pedagogy. Keywords: Arabic, Gamification, Gamilab, Interactive Learning Media, Learning Outcomes